The condomlessness of bareback sex: Responses to the unrepresentability of HIV in Treasure Island Media's Plantin' Seed and Slammed. (February 2015) - Scott, Stuart
This article focuses on the pornography produced by Treasure Island Media, specifically the two films Plantin' Seed (2004) and Slammed (2012), in order to explore and analyze the ways in which they alternately seek to represent HIV and to skirt its unrepresentability with metaphorical substitutes. The article posits a link between the function of the representation of the condom and that of condomlessness; it accordingly proposes a problematization of the representation of condomlessness within bareback pornography and argues that to represent condomlessness is fundamentally antithetical to what bareback pornography postulates and indeed believes about itself.